Answer:
x = 3±√5
Step-by-step explanation:
Given the quadratic equation;
0 = x² – 6x + 4
Swap sides
x² – 6x + 4= 0
Subtract 4 from both sides
x² – 6x + 4 - 4= 0 - 4
x² – 6x = -4
Complete the square;
Add the square of half of coefficient of x to both sides
Coefficient of x = -6
Half of Coefficient of x = -6/2 = -3
square of the half of Coefficient of x = (-3)²
Add (-3)² to both sides
x² – 6x + (-3)² = -4 + (-3)²
(x-3)² = -4 + 9
(x-3)² = 5
Take the square root of both sides
x - 3 = ±√5
x = 3±√5
This gives the solution to the equation